Implementation of extension workers for the tasks of agricultural extension programs in some governorates of Lower Egypt - Naser, Abdelghany Mohamed Abdeldayem; Hussein, Mohamed AbdelGhaffar ElBadrawy; Salem, Eman Mohammed Ebrahim (Journal of agricultural, environmental and veterinary sciences, 2023)
The research targeted the implementation of extension workers for the tasks of agricultural extension programs in some governorates of Lower Egypt. Data was collected using a personal interview questionnaire during the period from August to September 2022. The arithmetic mean, relative weight, Pearson’s simple correlation coefficient, and tabular presentation with frequencies and percentages were used as tools for statistical analysis. The most important actual results were as follows: 67.6% of the respondents have a weak executive level for the indicative tasks related to planning the indicative program, and 59% have a weak executive level for the indicative tasks related to the implementation of the indicative program, and that 60.5%It has a low executive level for extension tasks related to evaluating extension programmers. The results also showed that there is a significant and significant correlation between the degree of implementation of extension workers for various tasks and each of the following variables: job experience, number of years of work in agricultural extension, full-time extension work, renewal, job satisfaction. At a significant level (0.01), while the significant correlation was not confirmed with each of the academic specialization, job title, desire to work in agricultural extension.